2007
DOI: 10.1111/j.1440-1673.2007.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Capillary haemangioma involving the middle and external ear: Radiotherapy as a treatment method

Abstract: Capillary haemangiomas rarely occur in the auditory canal and have mainly been managed with surgical excision or kept on close follow up for development of symptoms. Radiotherapy, as a treatment method, has not been reported previously in the published work. We describe a study of a capillary haemangioma in the auditory canal of a 26-year-old woman who presented with bleeding. She was treated with radiotherapy, after the lesion was found to be unsuitable for surgery and embolization. The patient remains well 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Hemangiomas or angioendotheliomas are benign vascular tumors; they represent less than 0, 21% of all temporal bone tumors [1]. The temporal bone's hamngiomas have a predilection in three sites, which are by decreasing order of frequency, the geniculate ganglion, the internal auditory meatus, and the origin of the chorda tymapni [2, 3], we can explain this predilection by the vascular abundance in these sites [3, 4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemangiomas or angioendotheliomas are benign vascular tumors; they represent less than 0, 21% of all temporal bone tumors [1]. The temporal bone's hamngiomas have a predilection in three sites, which are by decreasing order of frequency, the geniculate ganglion, the internal auditory meatus, and the origin of the chorda tymapni [2, 3], we can explain this predilection by the vascular abundance in these sites [3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…Hemangiomas are rare benign tumors growing in soft tissues and bones, there are several types of hemangiomas including the capillary type, hemangiomas are relatively common in head and neck, but they are exceptionally reported in middle ear [1, 2]. …”
Section: Introductionmentioning
confidence: 99%
“…Kostrzewa et al described the use of CO 2 laser-assisted excision of tumour which reduced the risk of bleeding and allowed better visualisation [15]. Pavamani et al reported the first time use of radiotherapy as the primary treatment of an inoperable capillary haemangioma of external and middle ear with a 5 years recurrence-free period [16]. Recent, propranol has been used extensively in treating haemangiomas in other body regions.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the mass extended beyond ossicles to reach the attic and facial nerve canal. There are other solitary case reports of cavernous or capillary hemangiomas involving the middle ear and external ear canal [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%